Padrões e modelagem espacial dos tributos imobiliários em Belo Horizonte: uma ferramenta de auxílio ao planejamento urbano - Diego Ferreira Fonseca (2014)
There's been many discussions about multidisciplinary studies, especially those using modeling techiques, aiming to predict, forecast or simply produce academic knowledge. Planning activities in general have been follwing this tendency, by becoming increasingly multidisciplinary instruments. This paper aims to present a modeling proposal with the aim of discussing a vital tribute to the Brazilian cities: the IPTU. To think about urban planning using this tax, is to think holistically about the municipal planning. In that sense, this research aims at the development of a spatial model capable of estimating the level of disproportionality and disparity in tax burden from property tax in relation to an ideal "distribution model"m centered on the principles of faimes, justice and ability to pay tax. Although the paper discusses about the legal concepts and urban direct tax, that is an exploratory discussion, since this work has no propositional claims regarding the revision of the calculus of the property tax. It is only propositional in what pertains to the use of tax information and its spatial patterns for urban space.